MODEL PENGINTEGRASIAN SPENDING REVIEW DALAM PENGAMBILAN KEPUTUSAN ANGGARAN PADA KEMENTERIAN KESEHATAN REPUBLIK INDONESIA - Beni Ruslandi; Bahrullah Akbar; Aries Djaenuri; Deti Mulyati (GoAcademica Research dan Publishing, 2020)
Budget decision making at the Ministry of Health has not taken advantage of the results of the spending review conducted by the Ministry of Finance. This condition is indicated by there are still seven indicators of RPJMN Health that have not been achieved and still require hard work even though the realization of health spending continues to increase. Therefore, the focus of this study aims to explore a model of integrating spending review in budget decision making at the Ministry of Health. This study uses a qualitative approach with an exploratory method, where the researcher seeks to explore and build the phenomena under study in an effort to answer the problems formulated previously. The results of the study indicate that there are factors that hinder and support the integration of spending reviews in budget decision making at the Ministry of Health so that an appropriate strategy is needed in integrating the spending review.